2018
DOI: 10.12809/hkmj187303
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with 1-year mortality among patients with HIV-associated tuberculosis in areas with intermediate tuberculosis burden and low HIV prevalence

Abstract: Data are limited regarding risk factors for mortality among patients with human immunodeficiency virus (HIV)-associated tuberculosis (TB) in areas with low HIV prevalence and intermediate TB burden, such as the Western Pacific region. This study aimed to assess such risk factors in Hong Kong, which has an intermediate TB burden and low HIV prevalence. Methods: We conducted a retrospective cohort analysis of adult patients reported to the Hong Kong TB-HIV Registry between 2006 and 2015. Baseline characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
5
9
0
2
Order By: Relevance
“…It can be assumed that initiation of ART and TB treatment in very advanced disease is only partially effective. The present study results confirmed the strong and independent role of symptomatic HIV disease and low CD4 counts in predicting mortality (Aung et al, 2019;Chan et al, 2018), highlighting the need to implement earlier diagnoses of both diseases. No significant association with mortality was found for age, male sex, anemia, or undernutrition, which have been identified as significant predictors in other studies (Marcy et al, 2014;Naidoo et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…It can be assumed that initiation of ART and TB treatment in very advanced disease is only partially effective. The present study results confirmed the strong and independent role of symptomatic HIV disease and low CD4 counts in predicting mortality (Aung et al, 2019;Chan et al, 2018), highlighting the need to implement earlier diagnoses of both diseases. No significant association with mortality was found for age, male sex, anemia, or undernutrition, which have been identified as significant predictors in other studies (Marcy et al, 2014;Naidoo et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Patients were followed until the end of their TB treatment or death, whichever occurred first. Patients who were lost to follow-up, or who had their treatment classified as failure, success, or cured were censored based on the last visit outcome date available in the database [2] , [7] , [17] . Likewise, patients who were alive at the end of TB treatment were considered censored.…”
Section: Methodsmentioning
confidence: 99%
“…Globally 10.0 million people developed TB disease, and around 1.4 million deaths occurred from TB disease in 2019 [1] . Similarly, the reported mortality among TB patients from previous studies ranged from 7% to 33.4% [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] . In 2014, the World Health Organization formulated the End TB strategy with a target of a 90% reduction of the annual number of TB deaths by 2030 [1] , [3] .…”
Section: Introductionmentioning
confidence: 92%
“…Similar studies reported no significant variation in terms of mortality between male and female patients, but the proportion of death was higher in female patients. 16,31 Previous studies demonstrated insignificant variation in terms of mortality between new TB patients and relapses. 7,20,32 In this study previous TB treatment was considered a significant risk factor for mortality, which is in line with a study conducted in the southern region of Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%